KRITIK KOMERSIALISASI PRODUK MURABAHAH: KEUNTUNGAN BISNIS VS TUJUAN SYARIAH (Jurnal Ekonomi dan Bisnis, 2025)
This study critically analyzes the commercialization of Murabahah products in Islamic financial institutions in Indonesia. The research focuses on the imbalance between profit-oriented practices and the fundamental objectives of Sharia, which emphasize justice, transparency, and trustworthiness. Using a qualitative literature review method, this study explores the concept of Murabahah, its implementation in Islamic banking, the use of wakalah, the phenomenon of side-streaming, and academic as well as practitioner criticism regarding Murabahah’s dominance in financing portfolios. The findings indicate that Murabahah practices often deviate from DSN-MUI fatwas, particularly regarding ownership transfer, inappropriate use of murabahah bil wakalah, and margin determination based on interest rate benchmarks. These deviations risk transforming Murabahah into a conventional financing instrument with a disguised mark-up scheme. This study recommends strengthening Sharia compliance, enhancing price transparency, improving internal procedures, increasing public literacy, and harmonizing regulations to realign Murabahah with maqashid al-shariah.
Keywords: Murabahah; Commercialization; Deviation; Wakalah; Side-Streaming; Sharia Objectives